2022
DOI: 10.3389/fpsyt.2022.981357
|View full text |Cite
|
Sign up to set email alerts
|

Protective and risk factors of problematic smartphone use in preteens using panel study on Korean children

Abstract: BackgroundIncreased smartphone use by children and adolescents places them at higher risk of overdependence. The problematic smartphone use of preteens is rapidly increasing. The preteen period is one of considerable developmental change and the influence of problematic smartphone use should be identified by reflecting on this change and considering its social psychological factors.MethodsThis study employed a secondary analysis using data from the 10th (2017) to 11th (2018) wave of the Panel Study on Korean C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Moreover, previous literature found that internet addiction reinforces procrastination behaviours and severely reduces academic performance of adolescents [60], which may lead to increased academic stress [70], a vicious cycle of self‐reinforcement. Literature suggests that positive parent–child relationship [71], parental supervision and authoritative parenting behaviour [72], as well as friendship satisfaction and academic motivation [73], can be protective factors for the addictive use of smartphones. Moreover, available evidence suggests that establishing skills, such as planning, self‐monitoring, time management and proactive attitudes, as well as emotional awareness and emotional regulation in stressful situations, are effective strategies to improve and prevent procrastination behaviours [74].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous literature found that internet addiction reinforces procrastination behaviours and severely reduces academic performance of adolescents [60], which may lead to increased academic stress [70], a vicious cycle of self‐reinforcement. Literature suggests that positive parent–child relationship [71], parental supervision and authoritative parenting behaviour [72], as well as friendship satisfaction and academic motivation [73], can be protective factors for the addictive use of smartphones. Moreover, available evidence suggests that establishing skills, such as planning, self‐monitoring, time management and proactive attitudes, as well as emotional awareness and emotional regulation in stressful situations, are effective strategies to improve and prevent procrastination behaviours [74].…”
Section: Discussionmentioning
confidence: 99%
“…It is calculated by assigning scores of 0-3, and the total score for the seven items ranges from 0 points to 21 points, with higher scores indicating higher severity. The cutoff points of the scores are categorized as none/normal (0-4), mild anxiety (5)(6)(7)(8)(9), moderate anxiety (10)(11)(12)(13)(14), and severe anxiety (15)(16)(17)(18)(19)(20)(21). 34 In this study, the analysis was carried out by reclassifying the patients into two groups: the normal group and the anxiety group (mild, moderate, and severe anxiety).…”
Section: Dependent Variablesmentioning
confidence: 99%
“…Risk factors for PSU by adolescents include low socioeconomic status, poor academic performance, social isolation, body mass index (BMI), alcohol or smoking use, being exposed to adverse experiences, and mental health issues [ 9 - 11 ]. When adolescents are at increased risk for PSU due to inadequate self-control and difficulties in self-regulation, they are more likely to develop symptoms of dependence and addictive tendencies into adulthood [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation